Emotion regulation and substance use: A meta-analysis. (1st January 2022) - Weiss, Nicole H.; Kiefer, Reina; Goncharenko, Svetlana; Raudales, Alexa M.; Forkus, Shannon R.; Schick, Melissa R.; Contractor, Ateka A.
Abstract: There has been exponential growth in research on emotion regulation and substance use in the past decade. The current meta-analysis evaluated variability in the magnitude of the relation between aspects of emotion regulation and substance use. A search of PsycINFO, Embase, PubMed, CINAHL Plus, and PILOTS in December 2020 resulted in 6642 initial studies, of which 95 met inclusion criteria (association between emotion regulation and substance use was reported, participants were > 18 years old, article was in English). A total of 445 effects were obtained ( N  = 156, 025 participants; weighted M age = 29.31; 59.5% female; 66.1% White; 76.6% non-clinical). Emotion regulation and substance use were significantly related ( r  = 0.19; p  < 0.001; 95%CI [0.17, 0.20]). Emotion regulation abilities were generally more strongly related to substance use than emotion regulation strategies; this pattern was stronger for behavioral vs. cognitive abilities and extended to both negative and positive emotions. Relations were stronger for older and clinical samples; mixed effects were found for sex and no conclusive effects were found for race. Despite limitations of the existing literature (e.g., cross-sectional, self-reports), results indicated that the magnitude of the relation between emotion regulation and substance use varied considerably as a function of emotion regulation and substance use constructs and sample characteristics. Highlights: The emotion regulation and substance use relation was significant and small-to-medium. Emotion regulation abilities vs. strategies were more strongly related to substance use. Behavioral vs. cognitive abilities were more strongly related to substance use. Both negative and positive emotion regulation abilities were related to substance use. Relations were stronger for older and clinical samples; mixed effects were found for sex.